2016
DOI: 10.13033/ijahp.v8i3.448
|View full text |Cite
|
Sign up to set email alerts
|

ANALYTIC HIERARCHY PROCESS & ANALYTIC NETWORK PROCESS in SPORT: A COMPREHENSIVE LITERATURE REVIEW

Abstract: Since the invention of AHP/ANP, several literature review studies have been presented to summarize theoretical developments and different application areas of its techniques. The purpose of this study is to present a comprehensive literature review of AHP and ANP applications in the field of sports. A total of 62 sports related AHP and ANP articles were selected, categorized and analyzed in this study. The findings show that AHP and ANP techniques have successfully been used for performance evaluation of teams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…AHP allows to approach the decision making considering a breakdown and a comparison between criteria to determine weights and values. Even if analytical network process (ANP) admit dependent criteria (Saaty, 1996;Cheng and Li, 2004;Nisel and Özdemir, 2016), in this case, the whole process considered consists of independent criteria, as it is defined by a well-known methodology. Other methods were reviewed in this study, such as Promethee (Olson, 2001) and Vikor methods (Opricovic and Tzeng, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…AHP allows to approach the decision making considering a breakdown and a comparison between criteria to determine weights and values. Even if analytical network process (ANP) admit dependent criteria (Saaty, 1996;Cheng and Li, 2004;Nisel and Özdemir, 2016), in this case, the whole process considered consists of independent criteria, as it is defined by a well-known methodology. Other methods were reviewed in this study, such as Promethee (Olson, 2001) and Vikor methods (Opricovic and Tzeng, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Peneliti sudah menerapkan AHP terkait olahraga (Nisel & Özdemir, 2016), namun sangat sedikit para peneliti yang membahas kriteria yang sistematis, prosedur dan pengambilan keputusan menggunakan AHP dalam olahraga gulat.…”
Section: Pendahuluanunclassified
“…Emrouznejad and Marra (2017) and Behzadian, Otaghsara, Yazdani and Ignatius (2012) indicated that various studies used AHP and TOPSIS to make logistics decisions, however, making logistics decisions of sports clubs using AHP and TOPSIS is a novel area. According to a recent literature review by Nisel and Özdemir (2016), the application of AHP methods are mainly on performance evaluation of teams or coaches, player selection and ranking, the ranking of teams, clubs or coaches.…”
Section: Literature Reviewmentioning
confidence: 99%